2021
DOI: 10.1007/s10853-021-06467-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graphene nanoplatelets on the mechanical and gas barrier properties of woven carbon fibre/epoxy composites

Abstract: Carbon-fibre-reinforced polymer (CFRP) composites are promising materials for non-metallic pipe applications in the oil and gas industry owing to their high corrosion resistance, specific strength and stiffness. However, CFRP has poor gas barrier performance meaning that a liner has to be inserted. Graphene-based nanomaterials have been demonstrated to improve gas barrier properties in thermoplastic polymers, and thus, a CFRP–graphene hybrid composite could provide an alternative to lined pipes. In this work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 59 publications
(66 reference statements)
2
6
0
Order By: Relevance
“…However, their results showed that the mechanical properties of glass fiber/epoxy composites lead to significant improvements in flexural strength and mode I interlaminar fracture toughness using a GNP content of 0.25 wt%. A similar trend on flexural properties was also reported by Yao and coworkers [ 37 ] for carbon fiber/epoxy composite with relatively low GNPs content. This signifies that the optimal concentration of GNPs is essential to provide better mechanical properties on composite laminates.…”
Section: Resultssupporting
confidence: 87%
“…However, their results showed that the mechanical properties of glass fiber/epoxy composites lead to significant improvements in flexural strength and mode I interlaminar fracture toughness using a GNP content of 0.25 wt%. A similar trend on flexural properties was also reported by Yao and coworkers [ 37 ] for carbon fiber/epoxy composite with relatively low GNPs content. This signifies that the optimal concentration of GNPs is essential to provide better mechanical properties on composite laminates.…”
Section: Resultssupporting
confidence: 87%
“…Wang et al 43 stated that integrating graphene nanofiller in glass/epoxy composite enhances flexural strength since adding graphene improves the bending load carrying capacity and reduces the filler pull‐out and matrix crack propagation. Yao et al 72 studied the rupture mechanism of tensile and flexural tested graphene nanoparticles integrated with epoxy/carbon fiber composites, and the SEM images from the study conducted by Yao et al 72 are similar to results obtained from this study as shown in Figure 6.…”
Section: Resultssupporting
confidence: 79%
“…The agglomeration acts as a stress concentrator during loading, which causes early failure. Yao et al, 49 examine the fracture mechanism of mechanically tested grapheneadded carbon fiber/epoxy composites using SEM, whereas the results resemble those of earlier results that have been published.…”
Section: Fractography Observationmentioning
confidence: 54%